Attention‐driven read‐aloud technology increases reading comprehension in children with reading disabilities. (9th February 2021) - Schiavo, Gianluca; Mana, Nadia; Mich, Ornella; Zancanaro, Massimo; Job, Remo
Abstract: The paper presents the design of an assistive reading tool that integrates read‐aloud technology with eye tracking to regulate the speed of reading and support struggling readers in following the text while listening to it. The paper describes the design rationale of this approach, following the theory of auditory–visual integration, in terms of an automatic self‐adaptable technique based on the reader's gaze that provides an individualized interaction experience. This tool has been assessed in a controlled experiment with 20 children (aged 8–10 years) with a diagnosis of dyslexia and a control group of 20 children with typical reading abilities. The results show that children with reading difficulties improved their comprehension scores by 24% measured on a standardized instrument for the assessment of reading comprehension and that children with more inaccurate reading ( N = 9) tended to benefit more. The findings are discussed in terms of a better integration between audio and visual text information, paving the way to improve standard read‐aloud technology with gaze‐contingency and self‐adaptable techniques to personalize the reading experience. Lay Description: What is already known: People with dyslexia present problems in associating graphemes with phonemes and in mapping the sounds of language to letters and words. Reading‐aloud tools that combine text presentation with audio output have been proven to be beneficial for dyslexic readers. A limitation of these tools is that they do not keep track of the portion of text visually processed by the reader. Therefore, there may be incongruence between what the reader hears and what he/she is actually reading. What this paper adds: The study explores the use of a read‐aloud tool called GARY that combines eye‐tracking with read‐aloud technology. The key aspect is that the audio speed is automatically adjusted to keep up with the reading speed of the reader. A controlled study with primary school students investigates the use of the tool compared with traditional read‐aloud technology. The results show a positive effect on reading comprehension scores, especially for children with more inaccurate reading. Implications for practitioners: A better integration between audio and visual text information can support reading comprehension in children with dyslexia. Gaze‐regulated read‐aloud tools are a promising approach for supporting struggle readers. Such tools are promising for training readers with dyslexia in coupling audio and visual information.